Computer control of teaching enhancement by communication networked - Nada N. Tawfeeq; Mehdi J. Marie; Khalaf S Gaeid (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Enhancement of teaching and education is crucial. This enhancement is rapidly improved through combining communication and technology resulting in various benefits (particularly the wireless Technologies (WT)). Such combination encourages lecturers to meet the worldwide demand for changing traditional teaching techniques to technology-based methods. Wireless system networks (WSNs) represent systems of smart devices that arelinked wirelessly. In addition, these devices are characterized by having a bandwidth of bounded communication, abilities of sensing and computation. For performing operations of control, this system employs a Flywheel Position Control System (FW PCS) as a plant node. This study utilizes the True Time 1.5 MATLAB/Simulink platform for simulating and implementing the WSN mathematical model with wireless networks. The simulation is carried out between plant nodes and controller using the IEEE 802.15.4 standard (also called ZigBee) via protocols of Wi-Fi. The suggested E-learning model comprises a set of properties that can encourage and enhance the level of students in various learning purposes and stages.